Ende og Eine - Lien, Ragnvald (NAMN OG NEMNE, 2019)
This article deals with two versions of the farm name Ende in the municipality of Bærum, county of Akershus, Norway. The variant Eine is an oral version used for this farm. The appellative ende m. is the Norwegian word for end or edge and one explanation is the farm's location in the southern part and end of Lommedalen valley. Ende is the original farm name used in land registers and by the Norwegian Mapping Authority until 1971. The pronunciation of this particular farm's name is like eine similar to a possible plant name for juniper (Juniperus communis L.). Eine may have developed from an Old Norse appellative eini n. with the explanation 'an area covered with junipers'. The author of the monumental work 'Norwegian Farm Names' (Norske Gaardnavne) preferred this explanation. However, the appellative ende m. has a local pronunciation like eine in the county of Akershus. The author concludes that the name Ende in Bærum describes the farm's situation in the end of the Lommedalen valley.